Perancangan Aplikasi Pencatatan Kehadiran Online Berbasis Web - Popy Yuliarty; Saruni Dwiasnati; Hayu Kartika; Novera Elisa Triana; Candra Setia Bakti (CSRID (Computer Science Research and Its Development Journal), 2026)
Attendance recording is a crucial administrative activity in educational institutions because it is directly linked to discipline, reporting, and decision-making at the school level. However, manual attendance procedures are still widely used and often generate various problems, including delays in recapitulation, inconsistent data formats, potential duplicate records, and limited access to information required for periodic monitoring. In response to these issues, this study aims to design and evaluate a web-based online attendance application that supports a more systematic, measurable, and accountable attendance management process through login-based user authentication. The methodology includes a needs analysis involving key stakeholders administrators, homeroom teachers, subject teachers, and students which is then translated into a role-based system design. Subsequent stages comprise prototype development, functional testing to ensure feature compliance with specifications, and usability evaluation to assess ease of use and user acceptance. The developed application provides core functionalities such as role-based user management, daily attendance entry, input validation to minimize errors and prevent duplication, and change-history logging (audit trails) to strengthen data integrity and traceability. In addition, the system offers automated recapitulation and attendance trend visualization across daily, weekly, and monthly periods to make monitoring faster and more informative. The system is implemented as a web application using the Laravel framework and a responsive interface to ensure accessibility across multiple devices. Functional testing results indicate that the main features operate as intended, while usability evaluation suggests that the application is easy to use and improves work efficiency compared to manual procedures. Overall, the findings confirm that a web-based attendance system reinforced by data integrity mechanisms and periodic reporting can enhance monitoring effectiveness, accelerate recapitulation processes, and strengthen the accountability of attendance records in schools.